PENGARUH PEMBERIAN SOAL CERITA BERBASIS HOTS (HIGHER ORDER THINKING SKILL) TERHADAP HASIL BELAJAR MATEMATIKA SISWA SD NEGERI 2 TEMPILANG - Erliyana Andika Ayu; Destiniar Destiniar; Susanti Faipri Selegi (Universitas Negeri Medan, 2023)
The purpose of this study was to find out whether giving HOTS (Higher Order Thinking Skill) based word problems to students at SD Negeri 2 Tempilang can improve mathematics learning outcomes. This research method uses an experimental method with the Posttest-Only Control Design. The population in this study were fifth grade students. The sample in this study was 60 students. The sampling technique was carried out by means of simple random sampling. Test data collection techniques and documentation. Data analysis techniques in this study used the normality test (Kolmogorov-Smirnov), homogeneity test (F test), t-test (Independent Sample T-Test). The results of the calculation of data analysis obtained the average value of the control class posttest results of 58.20 and the experimental class posttest results of 81.83. So it can be concluded that giving HOTS (Higher Order Thinking Skill) based word problems to students at SD Negeri 2 Tempilang has an effect on their mathematics learning outcomes. Therefore, fifth grade elementary school students can use HOTS (Higher Order Thinking Skill) based word problems to improve their higher order thinking skills.Keyword: Influence, Story Problems, HOTS, Learning Outcomes, Mathematics Tujuan penelitian ini untuk melihat apakah pemberian soal cerita berbasis HOTS dapat meningkatkan hasil belajar matematika siswa. Metode penelitian ini menggunakan metode eksperimen dengan desain Posttest-Only Control Design. Populasi dalam penelitian ini adalah siswa kelas V. Sampel dalam penelitian ini berjumlah 60 siswa. Teknik pengambilan sampel dilakukan dengan cara simple random sampling. Teknik pengumpulan data tes dan dokumentasi. Teknik analisis data dalam penelitian ini menggunakan uji normalitas (Kolmogorov-Smirnov), uji homogenitas (uji F), uji-t (Independent Sample T-Test). Hasil perhitungan analisis data diperoleh nilai rata-rata hasil posttest kelas kontrol sebesar 58,20 dan hasil posttest kelas eksperimen sebesar 81,83. Maka pemberian soal cerita berbasis HOTS di SD Negeri 2 Tempilang berpengaruh terhadap hasil belajar matematika mereka. Oleh karena itu, siswa kelas V SD dapat menggunakan soal cerita berbasis HOTS guna meningkatkan kemampuan berpikir tingkat tingginya.Kata Kunci: Pengaruh, Soal Cerita, HOTS, Hasil Belajar, Matematika